Preparing Preservice Teachers by Building Content and Pedagogical Knowledge of Integrating Technologies - Morgan, Patrice (Journal of Education and Training, 2023)
After the declaration of Covid-19 outbreak in March 2020, the system of education changed from traditional field experiences to virtual environment of online learning. As per the need of time, this paper discusses the methods of online learning that learners and educators use to keep up with the flow of education. With the complete incorporation of technology in the educating system, the challenges and training support provided to preservice and in-service teachers is the vital essence to deliver beneficial impacts. However, delivering education with proper expertise in specialized software such as Google Classrooms, Zoom, TV school, online portals, Microsoft teams, and different social media platforms such as Facebook, Twitter, and Youtube, also requires learning materials to excel in terms of quality and accessibility. Hence, preservice teachers are being assisted by online forums, webinars, courses, and even degree programs to learn and develop their careers in a virtual context to prepare for their futures. Current research was conducted with over forty preservice teacher respondents which was consistent with a previous study of over one hundred pre service teacher participants. This article aims to highlight the current pandemic scenario and its impacts on the educational sector in the preservice teacher education programs and to discuss methods and measures currently in use to promote the technological way of learning and how the trainers are affected by it.